The Usefulness of Magnetic Resonance Angiography to Analyze the Variable Arterial Facial Anatomy in an Effort to Reduce Filler-Associated Blindness: Anatomical Study and Visualization Through an Augmented Reality Application - Mespreuve, Marc; Waked, Karl; Collard, Barbara; De Ranter, Joris; Vanneste, Francis; Hendrickx, Benoit (Aesthetic surgery journal. Open forum, 2021)
Abstract Background The use of soft tissue fillers for facial rejuvenation is increasing rapidly and the complications, unfortunately, follow the same path. Blindness caused by intravascular filler injections is a rare but devastating complication. Knowledge of the individual arterial anatomy may aid the injector in avoiding injecting into an artery and thus to prevent blindness. Objectives To evaluate if the use of magnetic resonance angiography (MRA) may visualize the arterial facial anatomy in a contrast- and radiation-free way and study the individual arterial variations using an augmented reality (AR) image. Methods The individual arterial anatomy of the 3 terminal branches of the ophthalmic artery (supraorbital [SO]; supratrochlear [STr]; and dorsal nasal [DN] arteries) of 20 volunteers was studied by a 3-Tesla MRI, combining infrared (IR) facial warming and 3-dimensional time-of-flight multiple overlapping thin slab acquisition MRA. The resulting visualization of the facial arteries was shown on the patient’s face through AR technology. Results The MRA was able to visualize the SO in 90.0%, STr in 92.5%, and DN arteries in 75% of the examined patients, as well as numerous variations in both vessel localization and path. Furthermore, a proof-of-concept of the AR visualization of the individual arterial anatomy was successfully implemented. Conclusions Dermal filler injectors should be aware of the risk of filler-induced blindness and familiarize themselves with the visualization of the variable facial vascular anatomy. The implementation of a one-time MRA and subsequent AR visualization may be useful in the accurate planning of minimally invasive facial rejuvenation procedures.